Long-term behaviour of GRP pipes - H. Faria (2005)
The main objective of the research programme /1/ described is the study of creep and relaxation behaviour of glass-rein forced thermosetting (GRP) pipes, in order to find alternative methods to predict the long-term properties, rendering a considerable reduction of the time needed for testing and assuring, as far as possible, equivalent reliability when compared to the existing methods. Experimental procedures were performed and are presented here, together with discussion of results, as well as predictive methodologies studied.